(untitled) (Comprehensive Journal of Science, 2025)
Marine pollution is one of the most important issues affecting all countries of the world, especially developing countries that lack modern and advanced means to reduce pollution in all its forms and causes, as the increased exploitation of the sea for transportation, whether for humans or transporting various goods, because it is one of the cheap means with a large load, in addition to the absence of law, which caused environmental, economic and security problems, which have become difficult to reduce or eliminate. The research aimed to identify the causes of pollution and evaluate the environmental impacts on the local environment, and propose sustainable solutions to overcome this problem. Study procedures; The descriptive approach was followed to trace the history of the emergence of pollutants and the time it takes to reduce their pollution. And it reached results. Among them is an attempt to catch up with the advanced world in developing methods of control; and following international laws and regulations to reduce its risks. The research concluded; that pollutants have effects that extend to many years and have a significant impact on marine life of all kinds, from plants, plankton, birds and fish, and reach humans through the food chain